2004
DOI: 10.1081/prg-200030315
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Severe Chronic Hypertension: Maternal Outcome

Abstract: Three-quarters of women with severe chronic hypertension in the second half of pregnancy developed superimposed preeclampsia. Intensive monitoring of the clinical status of the mother was associated with low maternal morbidity and the absence of maternal deaths. Pregestational chronic hypertension does not change the maternal prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 13 publications
2
10
0
2
Order By: Relevance
“…Vigil-De Gracia et al stated that eclampsia was not detected in women with superimposed preeclampsia suggesting different pathophysiological abnormalities leading to development of eclampsia in women with or without chronic hypertension. 9 The results of this study reinforced the hypothesis of Vigil-De Gracia et al Similar to our results; Vigil-De Gracia et al did not find any difference in preterm delivery at 37 weeks of gestation between the groups. They also suggested that perinatal outcomes after expectant management were not different in women with superimposed preeclampsia compared to severe preeclampsia.…”
Section: Discussionsupporting
confidence: 82%
“…Vigil-De Gracia et al stated that eclampsia was not detected in women with superimposed preeclampsia suggesting different pathophysiological abnormalities leading to development of eclampsia in women with or without chronic hypertension. 9 The results of this study reinforced the hypothesis of Vigil-De Gracia et al Similar to our results; Vigil-De Gracia et al did not find any difference in preterm delivery at 37 weeks of gestation between the groups. They also suggested that perinatal outcomes after expectant management were not different in women with superimposed preeclampsia compared to severe preeclampsia.…”
Section: Discussionsupporting
confidence: 82%
“…5 The main recommendation is to prevent BP increase during pregnancy through an improvement in dietary and lifestyle habits (also aimed at body weight control), while pharmacologic treatment is considered to prevent progression towards more severe disease and to improve maternal and fetal outcomes. 6 Indeed, while there are consistent data regarding the effect of severe hypertension on maternal and fetal morbidity and mortality as well as the effects of antihypertensive treatment in these hypertensive patients, [7][8][9] less is known about the risk predictors and the effect of pharmacologic treatment in patients with mild to moderate hypertension and the relative effect of antihypertensive treatment. 10 In this context, the main aim of our study was to evaluate the independent prognostic factors of maternal and fetal negative outcomes in a relatively large sample of normotensive pregnant women affected by chronic hypertension, gestational hypertension, or preeclampsia.…”
mentioning
confidence: 99%
“…14,15 Labetalol and nifedipine have similar hemodynamic effects and are also widely used. 16,17 Although some reports have indicated that sodium nitroprusside is also effective and safe when infused for short periods and at low doses, 18 obstetricians rarely prescribe nitroprusside and the experience of its use during pregnancy is very limited.…”
Section: Discussionmentioning
confidence: 99%